Gereja dan Demokrasi di Indonesia Berdasarkan Pemikiran A.A. Yewangoe dan Zakaria J. Ngelow - Sinuraya, Alosius Des Afriando (Faculty of Theology Duta Wacana Christian University, 2025)
AbstractA.A. Yewangoe and Zakaria J. Ngelow can be identified as theo-democratic thinkers—theologians who integrate the values of the Christian faith with the principles of democracy within the socio-political context of Indonesia. This study aims to examine their theological reflections on the relationship between the Church and democracy in Indonesia, particularly in promoting the values of justice, equality, and respect for human dignity as grounded in Pancasila. Both theologians underscore the Church’s vital role in the process of democratization: Yewangoe highlights the prophetic vocation of the Church as an agent of social transformation, while Ngelow emphasizes the Church’s contribution to the consolidation of Indonesian democracy as a component of civil society. Employing a descriptive-analytical approach, this study critically analyzes the major works of both figures. The findings indicate that the theological perspectives of Yewangoe and Ngelow offer a relevant and contextual framework for understanding the relationship between the Church and democracy in Indonesia, providing a constructive theological basis for public engagement and nation-building. AbstrakA.A. Yewangoe dan Zakaria J. Ngelow dapat dikategorikan sebagai pemikir teo-demokrat yaitu teolog yang mengintegrasikan nilai-nilai iman Kristen dengan prinsip-prinsip demokrasi dalam konteks sosial-politik Indonesia. Penelitian ini bertujuan mengkaji pemikiran Yewangoe dan Ngelow mengenai hubungan gereja dan demokrasi di Indonesia, khususnya dalam mempromosikan nilai-nilai keadilan, kesetaraan, dan penghormatan hak asasi manusia berdasarkan Pancasila. Kedua tokoh ini menekankan pentingnya peran gereja dalam proses demokratisasi di Indonesia, dengan Yewangoe menggarisbawahi peran profetis gereja sebagai agen transformasi sosial, sementara Ngelow menekankan kontribusi gereja dalam pembangunan demokrasi Indonesia sebagaibagian dari masyarakat sipil. Pendekatan yang digunakan dalam penelitian ini adalah deskriptifanalitis, dengan fokus pada analisis karya-karya kedua tokoh tersebut. Hasil penelitian menunjukkan bahwa pemikiran Yewangoe dan Ngelow dapat menjadi referensi atau basis teologis yang relevan dalam menjelaskan hubungan gereja dan demokrasi di Indonesia.